Retrofit Technics for Cyclic Behavior Improvement of RC Columns - Patricio Rocha (2008)
The main purpose of this paper is to present an experimental and numerical study concerning retrofit techniques on cyclic behavior of RC columns. The Laboratory for Earthquake and Structural Engineering (LESE) of the Faculty of Engineering of University of Porto (FEUP) is performing an experimental campaign on RC columns representative of typical buildings designed prior to 1980. Cyclic loading tests under constant axial load were carried out on specimens as built and after retrofit in order to assess the available capacity during seismic events and to define retrofit strategies compatible with actual safety levels. All studied specimens were retrofitted by different techniques based on either CFRP sheets or steel plates, bearing in mind the behavior and failure type obtained from the "as built" previous test. The description of retrofit design methodologies and application details are presented, highlighting for each case the main important aspects to achieve optimized retrofit strategies. The application of retrofit techniques was deliberately based on common practices as used on building rehabilitation. Some details are also given concerning the adopted testing setup in order to evidence the inherent advantages and limitations. In addition the adopted specimen instrumentation is described, showing that the result discussion is not only based on force and displacement response but also on dissipated energy.